AI tools and academic performance: engagement and motivation in social sciences education - Shahzeb; Sudrajat, Sudrajat; Sibghatullah (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
This study aims to examine the role of advanced AI tools, such as ChatGPT, on student’s academic performance. Additionally, it investigates the mediating role of student’s engagement and motivation in the relationship between AI tools and Academic performance in the department of Social Sciences Education at State University of Yogyakarta. This study has adopted a quantitative approach and has collected data from 52 undergraduate students enrolled in specified sample. Data analysis was conducted using SPSS. The findings indicate that AI tools significantly correlated with academic performance (r = 0.717, p < .01), while also  also showing positive correlation with student engagement (r = 0.692, p < .01) and motivation ( r = 0.658, p < 0.01). Furthermore, it improves comprehension of students, and provides self-directed learning. However, concern regarding over-reliance on AI is also identified, particularly its potential impact on critical thinking. This study highlights the importance of responsible AI integration, emphasizing the need to create balance between AI-driven learning and traditional methods. Educational Institutions must develop strategies that maintain student’s critical thinking and analytical skills while using AI tools. As a researcher, I believe the findings can assist institutions and instructors in implementing AI technologies into teaching practices in way that enhances academic performance, engagement, and motivation, while still fostering autonomous and critical thinking among students.